2023
DOI: 10.1371/journal.ppat.1011383
|View full text |Cite
|
Sign up to set email alerts
|

IFITM1 enhances nonenveloped viral RNA replication by facilitating cholesterol transport to the Golgi

Abstract: Aichi virus (AiV), a small non-enveloped RNA virus, hijacks the endoplasmic reticulum (ER)–Golgi cholesterol transport machinery to form cholesterol-rich replication sites originating from Golgi membranes. Interferon-induced transmembrane proteins (IFITMs) are antiviral restriction factors, whose involvement in intracellular cholesterol transport is suggested. Here, we describe the roles of IFITM1 in cholesterol transport that affect AiV RNA replication. IFITM1 stimulated AiV RNA replication and its knockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Viruses 2023, 15, 1993 2 of 16 IFITMs in their lipid composition, as evidence in support of both possibilities is present in the literature [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 77%
“…Viruses 2023, 15, 1993 2 of 16 IFITMs in their lipid composition, as evidence in support of both possibilities is present in the literature [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 77%
“…However, intriguingly, IFITMs have little or no effect on the Murine Leukemia Virus and arenaviruses such as the Lassa virus and lymphocytic choriomeningitis virus [23][24][25]. Furthermore, several studies have reported that IFITMs can promote infection by the human papillomavirus 16 [25], Aichi picornavirus [26], and human coronavirus OC43 [27,28].…”
Section: Introductionmentioning
confidence: 99%